2018
DOI: 10.1080/1755876x.2018.1443625
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of scatterometer and HF radar wind direction measurements

Abstract: Scatterometer winds are increasingly being used by Meteorological Services to validate and assimilate into their forecast models and re-analyses. In this paper AS-CAT wind directions obtained in coastal regions around Australia are compared with those derived from ground-based HF radar systems. Good agreement is demonstrated at wind speeds greater than 5m/s. At lower wind speeds scatterometer winds are not expected to be as accurate and the HF radar is probably measuring swell rather than wind direction. Examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In the literature, experiments on the validation of HFr wind direction have been generally carried out in wide coastal areas and over the ocean for periods from days to months [20][21][22][23][24][25][26]. The results show that several factors contribute to the accuracy of HFr wind measurements, the operational frequency being the most relevant one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, experiments on the validation of HFr wind direction have been generally carried out in wide coastal areas and over the ocean for periods from days to months [20][21][22][23][24][25][26]. The results show that several factors contribute to the accuracy of HFr wind measurements, the operational frequency being the most relevant one.…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor is wind speed. Different studies comparing HFr and in situ measurements concluded that the retrieval of the wind direction is not reliable under wind speeds below 5 m/s [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Those early installations in Mexico had a completely oceanographic research purpose (Flores-Vidal et al, 2011, 2018 but lacked operational continuity with gaps in the time series on the order of two to 3 months for the worse cases, and with absolutely no real time data transfer. In 2009 the four radars from UABC were installed in Todos Santos bay (100 km south from the United States-Mexico border) and for the first time provided a continuous real-time time series with reduced data gaps due to the ability of data quality control 24/7.…”
Section: Mexicomentioning
confidence: 99%
“…Up to today OCOMEX is still operational, producing two nested grids of sea surface currents, inside the Todos Santos Bay with resolution of 500 m and 15 min, and at the adjacent ocean (Southern California Coastal Current) with 3 km and 1 h of resolution ( Figure 8A). With almost 10 years of measurements with research purposes on the southern California shore (Flores-Vidal et al, 2015, 2018 has brought operational success which supports Mexican federal agencies as well as the academic sector.…”
Section: Mexicomentioning
confidence: 99%
See 1 more Smart Citation